Against theory : continental and analytic challenges in moral philosophy - Furrow, Dwight (Routledge, 1995)
Against Theory's is a remarkable synthesis of both the continental and analytical philosophical traditions around the subject of morality. Its singularity lies in its analysis of the implications postmodernism has had on ethics.